Synthesis and Certification of Lanthanum Oxide Extracted from Monazite Sand - Samin Samin; Suyanti Suyanti; Susanna Tuning Sunanti; Wisnu Ari Adi (Universitas Gadjah Mada, 2020)
Synthesis and certification of lanthanum oxide extracted from monazite sand have been carried out. This research aimed to increase the added value of monazite sand and obtain the lanthanum oxide in-house certified reference material (CRM). Synthesis of lanthanum oxide consists of several stages, namely: monazite sand digestion, rare-earth elements hydroxide [REE(OH)3] precipitation, Ce separation, Nd separation, lanthanum oxalate precipitation, and calcination. Certification of lanthanum oxide was carried out by determining the average concentration of the oxides and its uncertainty from the seven accredited laboratories by the ISO 35-2006 statistical method. Two other minerals in the lanthanum oxide analyzed by the XRD method were cerium hydroxide [Ce(OH)3] and neodymium yttrium oxide fluoride (Nd2Y2O3F16). Lanthanum oxide certified contains ten oxides, with the two highest concentrations of La2O3 (91.662 ± 0.007)% and Nd2O3 (3.949 ± 0.002)%. Lanthanum oxide has met the qualification in-house CRM since it contained water less than 1%, was homogeneous, stable, and certified. La2O3 concentration in the lanthanum oxide in-house CRM from CSAT-BATAN, Indonesia was not significantly different in comparison to that from the Department of Chemical Engineering, Srinakharinwirot University, Thailand. Lanthanum oxide extracted from monazite sand can be used as reference material in determining the lanthanum oxide quality from the pilot plant process.